Variation of system performance, quality control standards and adherence to international FDG-PET/CT imaging guidelines - Rausch, I.; Bergmann, H.; Geist, B.; Schaffarich, M.; Hirtl, A.; Hacker, M.; Beyer, T. (Nuklearmedizin - NuclearMedicine, 2014)
Aim: To gather information on clinical operations, quality control (QC) standards and adoption of guidelines for FDG-PET/CT imaging in Austrian PET/CT centres. Methods: A written survey composed of 68 questions related to A) PET/CT centre and installation, B) standard protocol parameters for FDG-PET/CT imaging of oncology patients, and C) standard QC procedures was conducted between November and December 2013 among all Austrian PET/CT centres. In addition, a NEMA-NU2 2012 image quality phantom test was performed using standard whole-body imaging settings on all PET/CT systems with a lesion-to- background ratio of 4. Recovery coefficients (RC) were calculated for each lesion and PET/ CT system. Resu lts: A) 13 PET/CT systems were installed in 12 nuclear medicine departments at public hospitals. B) Average fasting prior to FDG-PET/CT was 7.6 (4-12) h. All sites measured blood glucose levels while using different cut-off levels (64%: 150 mg/dl). Weight- based activity injection was performed at 83% sites with a mean FDG activity of 4.1 MBq/kg. Average FDG uptake time was 55 (45-75) min. All sites employed CT contrast agents (variation from 1 %-95% of the patients). All sites reported SUV-max. C) Frequency of QC tests varied significantly and QC phantom measurements revealed significant differences in RCs. Conclusion: Significant variations in FDG-PET/CT protocol parameters among all Austrian PET/CT users were observed. subsequently, efforts need to be put in place to further standardize imaging protocols. At a minimum clinical PET/CT operations should ensure compliance with existing guidelines. Further, standardized QC procedures must be followed to improve quantitative accuracy across PET/CT centres.
Keywords: PET/CT; FDG; Austria; protocols; quality control; multicentre